Kebijakan Penyiangan Koleksi Perpustakaan Pusat Penelitian Bioteknologi Lembaga Ilmu Pengetahuan Indonesia - Siti Elly Faisholyah; Rahmadani Ningsih Maha (Perpustakaan Nasional, 2021)
Library of Research Center of Biotechnology Indonesian Institute of Sciences (PPPB-LIPI) has been existing for 34 years. The collection development and improve progress in biotechnology science that has been growing rapidly, it is must a library to keep up transformation with this development in this age. The fact, the library’s out of date printed collection still exist. Because of that, it is necessary to review subject and physical library collection. This analysis’s aims to make a data for library collection weeding policy to know what type, subject and year of a library collection that is going to weed, library collection that is needed in the future and as tools collection development for furthermore, library collection development policy hereafter. This analysis uses survey method. Data collection is done which disseminates questionnaire to the researcher and literature study. The result shows that 40% of the printed collections are maintained with the textbook criteria of 55.9%. PPPB-LIPI is suggested to prioritize audio visual collections to 86.4%, the type of audio-visual acquisition is 39% computer files, 39% online information on the internet. Based on the publication’s year, 54.2% of the library collections weeding list are those over the past 15 years, fields outside of biotechnology that defended are chemistry at 64.2%. This research produces data to formulate collection weeding policies, namely the types of printed collections that is weeded immediately are journals, the subjects of the collections that defended are chemistry, pharmacy, animal husbandry, plants.